Simulation of the fatigue behaviour of a power plant steel with a damage variable - Lu, Jiawa; Sun, Wei; Becker, Adib A.; Saad, Abdullah Aziz (Elsevier, 2015)
The fatigue behaviour of a 9Cr power plant steel at a temperature of 600 °C was studied by uniaxial fatigue tests and microstructural analysis using electron microscopy. A continuum damage mechanics apporach was coupled to the constitutive equations of the Chaboche elasto-visco-plastic model to describe the fatigue behaviour of the 9Cr power plant steel at 600 °C. A stress partition method is introduced to understand the fatigue softening behaviour, and used to give an initial estimate of the material constants in the Chaboche model. Further optimisation procedures with plastic strain range dependency of the material constants were introduced in the optimisation procedure in order to accurately predict the material behaviour, especially after damage initiation. An ABAQUS UMAT subroutine was coded to allow the full life cyclic softening behaviour of a power plant component to be accurately predicted in a finite element calculation. The multiaxial capability of the coding is validated against notched bar test data.